STUDY OF SUSTAINABILITY AND CONFORMITY OF FUNCTIONING OF LOTIC ECOSYSTEMS ON THE EXAMPLE OF THE DZKNAGET RIVER (ARMENIA) (Proceedings of the YSU B: Chemical and Biological Sciences, 2017)
Hydroecological studies in different parts of the Dzknaget River were carried out in 2015–2017. Based on data of benthic macroinvertebrates spatial and temporal patterns of functioning of different ecotopes through river course have been revealed as well as the differences in sustainability have been discussed. The results of water quality assessment by different bioindication methods have shown that at all seasons water quality in the middlestream part was higher than in the downstream part. Also it’s been proved that the R. Dzknaget has low negative impact on Lake Sevan water quality.
Keywords: e Sevan, water quality, benthic macroinvertebrates, bioindication